Coupling 1D modifications and 3D nuclear organization: data, models and function. (February 2017) - Jost, Daniel; Vaillant, Cédric; Meister, Peter
Abstract : Over the past decade, advances in molecular methods have strikingly improved the resolution at which nuclear genome folding can be analyzed. This revealed a wealth of conserved features organizing the one dimensional DNA molecule into tridimensional nuclear domains. In this review, we briefly summarize the main findings and highlight how models based on polymer physics shed light on the principles underlying the formation of these domains. Finally, we discuss the mechanistic similarities allowing self-organization of these structures and the functional importance of these in the maintenance of transcriptional programs.